Pragmatic Study; The Use of Deixis in the Dee Lestari Coffee Philosophy Short Story Conversation Dialogue - Sofiea Anggraini; Dwi Fitria (Demagogi: Journal of Social Sciences, Economics and Education, 2024)
This research aims to analyze the use of deixis in dialogue between characters in the short story Filosifi Kopi by Dee Lestari. Meanwhile, the object is the use of deixis in dialogue between characters in the short story Filosofi Kopi by Dee Lestari. Research data was collected using document study techniques. The collected data was analyzed using descriptive-qualitative techniques. The results of the research show that there are 3 existing deixis, namely person deixis, place deixis, time deixis, and no discourse deixis was found in the dialogue. In place deixis it is possible that the pragmatic basis of place deixis is psychological distance. On the other hand, time deixis that is not included is calendar time and clock time. From the results that have been analyzed, persona deixis, place deixis, time deixis, in the dialogue between characters in the short story Filosofi Kopi by Dee Lestari, there are several words that are the same but have different purposes. Not all the same words have the same purpose, but there are some that have different purposes. The conclusions in this research are the results of the analysis of the dialogue in the short story Filosofi Kopi by Dee Lestari which has been described, found 8 persona deixis, 5 place deixis, 7 time deixis, and no discourse deixis found in the dialogue.